Age and performance from 10 seconds to a 6-days race - Marc, A.; Sedeaud, A.; Schipman, J.; Saulière, G.; Toussaint, J. F. (Journal of Athletic Enhancement, 2018)
Purpose: An increasing amount of people are turning to new challenges such as the completion of an ultra-marathon and choose to continue to train intensively despite advanced age. As a result, numerous epidemiological data are available and constitute an experimental model for the research community that studies the effects of aging on physiological functions. The objective of the study is to measure the relationships between age and performance over the entire athletic spectrum from 100 m up to the 6-day ultra-marathon event for men and women.